2021
DOI: 10.3892/etm.2021.10259
|View full text |Cite
|
Sign up to set email alerts
|

Whole‑body diffusion‑weighted magnetic resonance imaging and apparent diffusion coefficient values as prognostic factors in multiple myeloma

Abstract: Multiple myeloma (MM) is a neoplasm of the B lymphocytes characterized by the uncontrolled proliferation of a plasmocyte clone. Magnetic resonance imaging (MRI) remains the most sensitive and specific imaging method for the detection of bone marrow infiltration, before macroscopic bone changes are visible, with evidence that the detection rate and overall performance of MRI could be enhanced by applying diffusion-weighted imaging (DWI). The aim of our research was to evaluate whether measuring apparent diffusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
5
2
Order By: Relevance
“…31 Several studies have shown a prognostic value for the ADC value in multiple myeloma, as an independent prognostic predictor of PFS and OS. [32][33][34] However, this work indicated ADC was not an independent prognostic factor of HRMM by multivariate analysis. This might be because various factors affect the ADC value, including the number of yellow bone marrow cells, cell size, cell structure, and/or perfusion effects.…”
Section: Discussioncontrasting
confidence: 62%
“…31 Several studies have shown a prognostic value for the ADC value in multiple myeloma, as an independent prognostic predictor of PFS and OS. [32][33][34] However, this work indicated ADC was not an independent prognostic factor of HRMM by multivariate analysis. This might be because various factors affect the ADC value, including the number of yellow bone marrow cells, cell size, cell structure, and/or perfusion effects.…”
Section: Discussioncontrasting
confidence: 62%
“…It has been shown that lower ADC before treatment may be associated with better treatment response (13). This theory has may become one of the reasons why MM patients with lower ADC value obtained longer PFS and OS.…”
Section: Discussionmentioning
confidence: 99%
“…However, whether the imaging information about DW-MRI can predict the prognosis of MM patients and provide hints of disease management remains to be discussed. Some studies have found that the change of ADC value could reflect the response to disease treatment before the size and number of MM bone lesion (12,13). MM patients with nonequivalent bone lesions on DW-MRI mean worse prognosis than those negative ones (14).…”
Section: Introductionmentioning
confidence: 99%
“…Yamada et al [22] found that ADC value of MM treatment responders differed more significantly than that of non-responders (0.154 ± 0.386 × 10 −3 mm 2 /s vs –0.307 ± 0.424 × 10 −3 mm 2 /s, P = .003). In addition, it has been proved that ADC value was negatively correlated with survival time (r = –0.641, P < .001) [23] . As for the treatment response of PD, the average ADC value increased after treatment, but there was no statistical significance compared with the ADC value before treatment.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, it has been proved that ADC value was negatively correlated with survival time (r = –0.641, P < .001). [ 23 ] As for the treatment response of PD, the average ADC value increased after treatment, but there was no statistical significance compared with the ADC value before treatment. In 9 cases of PD, the increase of ADC value after treatment was slight in most patients, and even increased in some cases after treatment.…”
Section: Discussionmentioning
confidence: 99%